Identification and Interpretation of Metaphors in the Document Titles - Sharada, B. A. (Journal of Information and Knowledge, 1999)
A study of metaphors, is made with their characteristic features and the types. The article deals with the identification and interpretation of metaphosical titles with numerous examples. Finally, the job of the indexer is identified.